2007
DOI: 10.1007/s10286-007-0421-4
|View full text |Cite
|
Sign up to set email alerts
|

Vagal and sympathetic heart rate and blood pressure control in adult onset PHOX2B mutation–confirmed congenital central hypoventilation syndrome

Abstract: In summary, we found a reduced cardiac baroreflex and a blunted sympathetic mediated response in the individual with adult-onset CCHS, possibly due to dysfunction in the afferent pathway. Our results confirm that PHOX2B affects the development of the autonomic nervous system, possibly causing absence of normal maturation of carotid body and visceral sensory ganglia and leading to autonomic dysfunction in adult-onset CCHS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Though the term ''congenital'' as used in CCHS historically connoted presentation in the newborn period, patients presenting with later-onset CCHS (LO-CCHS) have been described. [18][19][20][21][22][23][24][26][27][28]57,72 With increased awareness of CCHS, discovery that PHOX2B is the disease-defining gene for CCHS, and recent availability of diagnostic tests for PHOX2B mutations, an increase in diagnosis of LO-CCHS with presentation in later infancy, childhood, and adulthood is anticipated.…”
Section: Autosomal Dominant Inheritance Of Cchs and The Phox2b Mutationmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the term ''congenital'' as used in CCHS historically connoted presentation in the newborn period, patients presenting with later-onset CCHS (LO-CCHS) have been described. [18][19][20][21][22][23][24][26][27][28]57,72 With increased awareness of CCHS, discovery that PHOX2B is the disease-defining gene for CCHS, and recent availability of diagnostic tests for PHOX2B mutations, an increase in diagnosis of LO-CCHS with presentation in later infancy, childhood, and adulthood is anticipated.…”
Section: Autosomal Dominant Inheritance Of Cchs and The Phox2b Mutationmentioning
confidence: 99%
“…2,[4][5][6][7][8][9][10][11][12][13][14][15][16][17] CCHS is characteristically diagnosed in the newborn period, yet we now know that cases can be diagnosed later in infancy and childhood [18][19][20][21] as well as adulthood. 20,[22][23][24][25][26][27][28] To best convey the remarkable history of CCHS, and to describe the value of recognizing CCHS as a model for translational (bench to bedside) and transitional (childhood to adulthood) autonomic medicine, we present this review article in the format of a chronological story, from 1970 to the present day.…”
mentioning
confidence: 99%
“…An increase in E:I ratio in the present study is indicative of an increase in parasympathetic infl uences. However, Valsalva ratio, which is yet another index of parasympathetic functions, did not change during hyperoxic hypobaria, most likely due to the complex nature of the response to the Valsalva maneuver, which involves both vagal and sympathetic pathways ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the June 2007 issue of Clinical Autonomic Research Diedrich and colleagues, from the Autonomic Dysfunction Centre at Vanderbilt University in Nashville, studied an adult patient with 20/25 PHOX2B genotype and alveolar hypoventilation [1]. They recorded blood pressure, heart rate and muscle sympathetic nerve activity and found that heart rate variability and cardiac baroreflex sensitivity were reduced and that the increases in muscle sympathetic nerve activity to the Valsalva maneuver, hypoxemia, isometric exercise and the cold-pressor test were attenuated.…”
Section: The Homeobox Genementioning
confidence: 98%